Engineering biological wastewater treatment for the removal of hazardous chemicals. - Mensah, Lawson (Cranfield University, 2019)
The European Union’s Environmental Quality Standards (EQS) continue to be stringent with regards to discharge of hazardous chemicals (HCs) (mainly organic micropollutants) from wastewater treatment plants (WWTPs). The strict limits are driven by the growing interest in wastewater reuse, evidence of feminisation of male aquatic species and bioaccumulation of HCs in water-based biota. WWTPs are the last barrier to these chemicals getting into the environment from homes, institutions and industries and therefore optimisation of existing WWTPs is critical. The operational conditions of the WWTPs such as solid retention time (SRT), hydraulic retention time (HRT), dissolved oxygen (DO) concentration and seasonal temperature variations have been proven to influence the removal of these HCs and also affect the microbial/bacterial diversity in WWTPs. This study therefore aimed to find the missing link in the literature, which is to seek the relationship between the microbial/bacterial diversity or abundance and HCs removal in WWTPs. A pilot-scale study was conducted to analyse the microbial and bacterial diversity using phospholipids fatty acid and 16S rRNA analysis respectively at 3, 10 and 27 d SRT (at constant 8 h HRT) and then repeated at a fixed 27 d SRT while HRT varied at 8, 16 and 24 h. The concentrations of nonylphenols and estrogens in the influent and effluent were also analysed using LC-MS/MS to determine the plant’s chemical removal efficiency. The results showed that raising SRT (from 3 to 27 d) and HRT (from 8 to 24 h) increased bacterial diversity by 2.7 times and increased the removal of EE2 by 11%. The pilot-scale also revealed 32 novel positive correlations between bacterial genera abundance and HCs removal. The abundances of Hyphomicrobium, Mesorhizobium, Planctomyces, and Rhizomicrobium positively correlated with the removals of estrogens (E1, E2 and E3) and with nonylphenols (NP₂ EC, NP ₅EO) at r- values >0.7. The experiment was repeated by surveying the bacterial diversity in 12 full-scale activated sludge plants (ASPs) operating at varying DO levels, SRTs (4.9 to 22.3 d), HRTs (6.2 to 26.6 h) and temperature (10.6 to 20.3 ˚C). The concentrations of 26 micropollutants (analgesics, antibiotics, anti-depressants, beta-blockers, estrogens, flame retardants etc.) were also analysed in the influent and effluent. The results showed that bacterial diversity in the full- scale reactor differed from that of the pilot-scale plant. Euclidean distance matrix shows that temperature (p<0.005) was the most influential parameter in chemical removal and bacterial diversity. SRT and HRT were also important in bacterial diversity and HC removal but not in every ASP. Removal of HC followed a pseudo first order kinetics with metformin and ibuprofen achieving >98% removals. DO concentration did not show any effect due to lack of variation across the WWTPs. Once again, some novel correlations between bacterial genera abundance and chemical removal were found. The abundances of Candidatus Accumulibacter (a phosphate accumulating bacteria capable of denitrification) and Nitrosomonas (nitrite-oxidising bacteria) correlate positively with the removal of trixylenyl phosphate (flame retardant) at R>0.7. Anaeromyxobacter dehalogenans abundance also correlates positively with the removal of erythromycin. This work has shown that process parameters do influence both bacterial diversity and hazardous chemical removal, and there are correlations between bacteria taxa abundance and HCs removal. This knowledge will be vital in the discussion on improving existing activated sludge plants achieve better chemical removal and it will also be the foundation for future research into correlations of bacterial taxa abundance with chemical removal in the ASP reactor.
Keywords: Microbial/bacterial diversity; phospholipids fatty acid; nonylphenols; estrogens; plant chemical removal efficiency; bacterial genera abundance